Antiretroviral switching and bedaquiline treatment of drug-resistant tuberculosis HIV co-infection. Issue 3 (March 2019) - O'Donnell, Max R; Padayatchi, Nesri; Daftary, Amrita; Orrell, Catherine; Dooley, Kelly E; Rivet Amico, K; Friedland, Gerald
Summary: Bedaquiline, a potent new therapy for drug-resistant tuberculosis, results in improved survival including in HIV patients with multidrug and extensively drug-resistant tuberculosis. In line with WHO recommendations, in South Africa and other low-income and middle-income settings, antiretroviral therapy is switched from generic fixed-dose combination efavirenz-containing regimens to twice-daily nevirapine with separate companion pills because of interactions between efavirenz and bedaquiline. Early data suggest a signal for low antiretroviral therapy adherence after this antiretroviral therapy switch. Mortality and other tuberculosis-specific benefits noted with bedaquiline treatment in multidrug and extensively drug-resistant tuberculosis HIV might be compromised by HIV viral failure, and emergent antiretroviral resistance. Programmatic responses, such as adherence support and dual pharmacovigilance, should be instituted; antiretroviral therapy initiation with fixed-dose combinations without bedaquiline drug interactions should be strongly considered.